Synthesis and characterization of Ni/AC catalyst derived from empty fruit bunch for methane dry reforming - Izzatul Aqilah, Mohd Amijar; Mazni, Ismail; Asmida, Ideris (IOP Publishing, 2025)
Greenhouse gas emissions are among the most pressing issues of the twentyfirst century. Methane (CH₄) and carbon dioxide (CO₂) can be converted into synthesis gas (syngas) via methane dry reforming (MDR), offering a viable solution. Nickel (Ni) catalysts, commonly used for MDR, face challenges like metal sintering and carbon deposition at high temperatures. This study investigates the use of activated carbon (AC) obtained from empty fruit bunches (EFB) derived from oil palm waste as a sustainable catalyst support for Ni in MDR. AC supports were prepared by pyrolysis at 700 and 800 °C for 30 min. Ni/AC catalysts with varying Ni loadings (1%, 3%, 5%, and 10%) were synthesized via the wet impregnation method. Consequently, the catalysts were identified utilizing Brunauer-Emmett-Teller (BET), thermogravimetric analysis (TGA), field emission scanning electron with energy dispersive X-ray spectroscopy (FESEM–EDX), as well as X-ray diffractometer (XRD) analysis. MDR experiments were conducted at 800 °C for 8 h with a CH4/CO₂ ratio of 1:1 using a fixedbed reactor. Catalysts were pre-reduced having 25% hydrogen/nitrogen (H₂/N₂) at 800 °C for 60 min. Product analysis was performed every 60 min using gas chromatography. The 3% Ni/AC catalyst pyrolyzed at 800 °C showed the highest CH₄ (28.86%) and CO₂ (52.79%) conversions. The results demonstrate the potential of AC derived from EFB as a catalyst support for syngas production via the MDR process as it exhibits a well developed porous structure with uniformly distributed Ni across the AC surface.